Expression, Purification, and Preliminary Characterization of Putative Protein Tyrosine Phosphatase Oca1 - Patel, Madhu; Kumar, Ashutosh; Zhang, Kam Y.J.; Akhtar, Md. Sohail (Protein and Peptide Letters, 2025)
Introduction/ObjectiveProtein phosphatases act as counterparts to protein kinases and are considered crucial for the homeostatic balance of cell signalling. In contrast to kinases, which can be categorized according to their substrate specificity, phosphatases are versatile and can detect substrates with much less distinction; hence, it is challenging to identify the physiological phosphatase-substrate pair. The Oca1 of Saccharomyces cerevisiae is a putative protein tyrosine phosphatase (PTP) and is required for cell cycle arrest in response to oxidative stress. The Oca1 mutants are sensitive to mTOR inhibitors, such as caffeine and rapamycin, and are involved in the regulation of TOR function. In an earlier research work, the enzyme exhibited no in vitro phosphatase activity and it was suggested that post-translational modifications or additional factors are necessary for it to be functional.MethodsThe modeling of Oca1 was performed to gain insight into the structural aspects. The full-length enzyme, as well as the enzyme without the N-terminal extension, was cloned, expressed, and purified to homogeneity. The structure, function, and stability of the purified enzyme were assessed using circular dichroism, fluorescence, and visible spectroscopy studies.ResultsThe Oca1 was expressed and purified from Escherichia coli. The enzyme has been found to be functional, stable, and exist in an extended monomeric form, with a molecular mass of about 27 kDa. The enzyme without the extended N-terminal random coil has also been functional and slightly more stable than the full-length Oca1.ConclusionThe purified functional enzyme may be used to gain insights into the biochemical aspects and its role in bioengineering.
Keywords: Protein tyrosine phosphatase